Identifikasi Platform dan Faktor Sukses dalam Manajemen Proyek Teknologi Informasi - Riesna, Deby Mega Rizkia; Pujianto , Dimas Eko; Efendi, Alvin Junio Ilham; Nugroho, Bagus Aji; Saputra, Dhanar Intan Surya (Jurnal Teknologi Riset Terapan, 2023)
Purpose: Success is something that is always expected, both success in the process and success in achieving goals. Many factors need to be considered to achieve success. One of the things that can help us succeed is how we manage the work we carry out. We must pay close attention to project management for the success of a project. Some platforms can help us carry out project management functions in an increasingly sophisticated era. Methodology/approach: This research is based on a systematic literature review (SLR). Among them are searching for related scientific articles using search tools such as Google Scholar, IEEE, Science Direct, ELSEVIER, and others using specific keywords. Results/findings: Based on the studies that have been carried out, it can be seen that there are tools for information technology (IT) Project Management and explain some of the Success Factors in IT Project Management. Conclutions: This study shows that the success of IT projects depends on effective project management and the use of appropriate tools. Several platforms support project execution, and key success factors include communication, stakeholder involvement, and technical skills. Choosing the right tools and managing well are essential to achieving project success. Limitations: This study can answer some of the questions that arose for discussion. Q1: What are IT tools for project management? Q2: What influences success in IT management projects? Contribution: This study aims to find software to help the project management process and factors that hinder and support IT projects.